Comparison of 2-Hour Oral Glucose Tolerance Test and Hemoglobin A1C in the Identification of Pre-Diabetes in Women with Infertility and Recurrent Pregnancy Loss - Alice J Shapiro; Emily C Holden; Peter G McGovern; Donald Alderson; Sara S Morelli (SAGE Publishing, 2019)
Research question: Does hemoglobin A1C (HbA1C) predict pre-diabetes (pre-DM) in a population of women with infertility and/or recurrent pregnancy loss (RPL), when considering the 75 g, 2-hour oral glucose tolerance test (2h GTT) as the gold standard? Design: Retrospective study of 242 patients with infertility or RPL presenting to a university-affiliated reproductive endocrinology and infertility clinic between January 2012 and December 2016 who underwent screening for disorders of glucose metabolism with a 2h GTT. The prevalence of pre-DM as defined by HbA1C 5.7% to 6.4% and 2h GTT values of 140-199 mg/dL, and predictive values of HbA1C for the identification of pre-DM when compared with 2h GTT, were calculated and compared. Results: Of 242 patients, 188 (77.7%) women had both HbA1C and 2h GTT performed. Of these, 89 (47.3%) tested positive for pre-DM by one or both methods. Of 89 patients, 14 (15.7%) had both an abnormal 2h GTT and an abnormal HbA1C. Only 6 out of 89 (6.7%) patients tested positive for pre-DM by an abnormal 2h GTT in the setting of a normal HbA1C result. Conversely, 69 of these 89 patients (77.5%) tested positive for pre-DM by an abnormal HbA1C in the setting of a normal 2h GTT. The prevalence of pre-DM, as defined by 2h GTT, was 10.6% (20/188) (95% CI, 6.6-16.0), compared with a prevalence of 44.1% (83/188) (95% CI, 36.9-51.6) when pre-DM was defined by HbA1C alone. When the 2h GTT was considered the gold standard for the identification of pre-DM, the negative predictive value (NPV) of HbA1C compared with 2h GTT was 94.3% (95% CI, 88.0-97.9), whereas the positive predictive value (PPV) of HbA1C compared with 2h GTT was only 16.9% (95% CI, 9.5-26.7). Conclusions: Although a normal HbA1C was highly predictive of a normal 2h GTT, the two tests demonstrate poor agreement in the identification of pre-DM in women with infertility and/or RPL. Hemoglobin A1C is superior to the 2h GTT as an initial screening test for pre-DM in this population, since it identified a substantial number of women who would otherwise remain undiagnosed in the setting for a normal 2h GTT alone. However, the long-term clinical relevance of an elevated HbA1C in this population needs to be better defined.